Effects of Thermodynamic Pairing on Nuclear Level Density - Hung, Nguyen Quang; Dung, Dang Thi; Trong, Tran Dinh (Communications in Physics, 2013)
Thermodynamic properties of some selected even-even nuclei such as ^56Fe, ^60Ni, ^98Mo, and ^116Sn are studied within the Bardeen-Cooper-Schrieffer theory at finite temperature (FTBCS) taking into account pairing correlations. The theory also incorporates the particle-number projection within the Lipkin-Nogami method (FTLN). The level densities are derived based on the statistical theory of the grand-canonical ensemble (GCE). The results obtained are compared with the recent experimental data by Oslo (Norway) group. It is found that pairing correlations have significant effects on nuclear level density, especially at low and intermediate excitation energies.